The Return Variation on Investment as a Function for the Difference of Market Share: An Applied Research on a Sample of Private Banks listed in Iraq Stock Exchange (ISX) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research specified with study the relation  between the market share for the sample research banks and the amount of the achieved revenues from the investment, where the  dominated belief  that there potentiality enhancing the revenue on investment with the increase of the banks shares in their markets after their success in achieving rates of successive growth in their sales of sales and to a suitable achieve  market coverage for their products and they have dissemination and suitable  promotion activity, the  market share represented the competition  for the banks, and the markets pay attention to the  market share as a strategic objective and to maintain them also increasing them at a certain  marketing conditions, where the market share effects positively in the revenue rate on investment, and at the final station, the research has reached several conclusions and recommendations , and the most important of them are:- the research results has proved, in their final form, the significance  effect of market share in the profits of the banks of the sample research after the results have proved that there is positive relation between the  market share and the investment revenue and any increase in the market share for the sample research sample resulted in  increase in the profit levels with the  significance of revenue on the investment in the stocks  reverse to that, it supports the research hypothesis. The researcher recommends to investigate methods of increasing the banks shares from their sales and positioned advanced locations guarantee achieving a substantiated competitive